Combined composites layup architecture and mechanical evaluation of type IV pressure vessels: A novel analytical approach. (29th May 2023) - Jiang, Weili; Du, Fengmin; Drechsler, Klaus; Zheng, Jinyang
Abstract: Strict requirements for cost and reliability of compressed gaseous pressure vessels as on-board hydrogen storage necessitates in-depth understanding on the mechanical responses of the composite structure. General numerical methodology to assess this involves a two-step setup: composite layup generation and mechanical property calculation, which becomes highly time and resource-consuming, particularly if multiple designs are scanned for optimization. This study presents a multi-functional analytical tool, combining both aforementioned steps in a single modeling framework. The model enables quick prediction of the strain/stress distribution in correlation with uncomplicated inputs describing the layup design, i.e. stacking sequence with desired winding angles. Additionally, the mechanical evaluation specially focuses on the dome region whose calculation has hardly been inspected analytically in the literature. The results are validated against a three-dimensional finite element calculation implemented in Ansys Workbench, showing qualitative and quantitative agreement. Overall, the study paves the way for composite tank design using analytical approaches, with easy implementation, minimum computational cost and great transparency. Graphical abstract: Image 1 Highlights: Analytical model combining composite layup generation and mechanical evaluation. Model accuracy is verified vs. a 3D Finite Element simulation of pressure vessel. Flexibility and speed of the model enables evaluation of specific tank design. Focus on the dome whose evaluation has hardly been inspected analytically before.